Math, asked by SharmaShivam, 1 year ago

Simplify:
\dfrac{tan\left(x-\dfrac{\pi}{2}\right).cos\left(\dfrac{3\pi}{2}+x\right)-sin^3\left(\dfrac{7\pi}{2}-x\right)}{cos\left(x-\dfrac{\pi}{2}.tan\left(\dfrac{3\pi}{2}+x\right)}

Answers

Answered by Anonymous
13

Answer:

sin²x

Step-by-step explanation:

=> tan(x - π/2) = - tan(π/2 - x) = - cot x

.°.tan(x - π/2) = - cot x

=> cos(3π/2 + x) = cos(x - π/2) = cos(π/2 - x) = sinx

.°.cos(3π/2 + x) = sin x

=> sin(7π/2 - x) = sin(-π/2 - x) = - sin(π/2 - x) = -cosx

.°.sin³(7π/2 - x) = - cos³ x

=> cos(x - π/2) = cos(π/2 - x) = sinx

.°.cos(x - π/2) = sin x

=> tan(3π/2 + x) = tan(x - π/2) = - tan(π/2 - x) = -cotx

.°.tan(3π/2+x)= - cot x

Now, putting the values.

=> (- cot x). sin x + cos³x / sin x.(- cot x)

=> - cos x + cos³x / - cos x

=> (1 - cos²x)

=> sin²x ANSWER

Answered by ITzBrainlyGuy
7

ANSWER:

Taking the first term from the question

 \small{ \sf{ tan( x - \dfrac{\pi}{2}) =  - tan( {90}^{ \circ}  - x) =  - cot  \: x}}

.°. - tan(90° - x) = - cot x

Taking the second term from the question

 \small{ \sf{cos( \frac{3\pi}{2}   +  x) = cos( {270}^{ \circ}   +  x) =   sin \: x}}

.°. cos(270° + x) = sin x

Taking the third term from the question

\small{\sf{ -  {sin}^{3}( \frac{7\pi}{2}  - x) =   - [ -   {sin}^{3}({90}^{ \circ} - x) ]=cos^{3} \: x   }}

.°. - sin³(90° - x) = cos³ x

Taking the fourth term from the question

 \small{  \sf{cos( x - \frac{\pi}{2} ) =  cos( \frac{\pi}{2}  - x) =   sin \: x}}

.°. cos(90° - x) = sin x

Taking the fifth term from the question

 \small{ \sf{tan( \frac{3\pi}{2} + x) = tan( {270}^{ \circ} + x) = - cot \: x   }}

.°. tan(270° + x) = - cot x

Substituting the values

We get,

 \small{ \sf {=   \frac{  - cot \: x.sin \: x  +  {cos}^{3}x}{ sin \: x.( - cot \: x)} }}  \\   = \small{ \sf{ \frac{ -  \frac{cos \: x}{sin \: x}.sin \: x +  {cos}^{3} x }{sin \: x \times  ( - \frac {cos \: x}{sin \: x} )} }} \\ \small { \sf{ =  \frac{ - cos \: x +  {cos}^{3} x}{ - cos \: x } }} \\  \small{ \sf{ =  1 + \frac{  -  {cos}^{2}   x(cos \: x)}{cos \: x} }} \\ \small { \sf{ = 1 -  {cos}^{2}x }}  \\ \small{ \sf{ =  {sin}^{2}x }}

Similar questions